SOCIO-PSYCHOLOGICAL FEATURES OF THE FORMATION OF ADOLESCENT SPIRITUALITY (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
This article is a scientific observation based on the data collected on the basis of research in the field of social psychological significance of moral norms in adolescents, mainly analyzes the relationship between the psychological views of foreign psychologists in this area. a conclusion is made on the results obtained on the basis of the research method.